Effect of magnetic field on salicylic acid, ascorbic acid mediated germination and seedling parameters of rice (Oryza sativa L.) under salinity stress: Magnetic-Salicylic-Ascorbic effects salinity in rice - Mendu, Tejakumar; Dayal, Abhinav (ORYZA-An International Journal of Rice, 2025)
The study titled "Effect of Magnetic Field on Salicylic Acid and Ascorbic Acid-Mediated Germination and Seedling Parameters of Rice (Oryza sativa L.) Under Salinity Stress" was conducted during the Kharif season of 2023 at the Seed Testing Laboratory, Department of Genetics and Plant Breeding, SHUATS, Prayagraj, Uttar Pradesh. The experiment was designed using a Completely Randomized Design (CRD) with twelve treatments, including a control, replicated four times across four different salinity stress levels. The research focused on two rice varieties, "PB-1847" and "PB-1885," with "PB-1847" exhibiting superior performance compared to "PB-1885." Results showed that under control salinity (0 mM), the highest germination percentage (98.67%), root length (20.83 cm), shoot length (20.89 cm), seedling length (41.72 cm), fresh weight (1.12 g), dry weight (0.25 g), vigor index-I (4116.83), and vigor index-II (24.64) were achieved with treatment T8, which involved a magnetic field (200 mT) combined with salicylic acid (0.5 mM) for 10 minutes followed by a 12-hour incubation. This treatment significantly outperformed all other treatments and salinity stress conditions. The second-best results were observed with treatment T7, which used a magnetic field (150 mT) and salicylic acid (0.5 mM) under the same salinity condition. Conversely, the lowest values for these parameters were recorded under the control treatment (T0) with high salinity (150 mM). This finding suggests that salinity stress disrupts seed and seedling growth, but combining salicylic acid with a magnetic field mitigates these effects by improving germination rates, seedling length, and dry matter content. This combination enhances seedling vigor and presents a promising approach for improving rice cultivation under saline conditions. Utilizing this method for seed priming could significantly boost resilience and productivity in rice varieties facing environmental stress.